Evaluating the story of the United States as told through the United States History and Government Regents Exam: omissions, obscurations, and oppressions in a mandatory New York State high school assessment - Newman, Lori-Ann (Kansas State University, 2023)
The United States history survey course is a standard high school history class in the state of New York. The academic goal is for students to understand key people and developments that molded the United States into its modern identity as a progressive, democratic nation-state. This research examined one manifestation of this course in New York State, the United States History and Government Regents exam. The United States History and Government Regents exam is a mandatory, standardized assessment usually taken by high school juniors after completing their annual survey U.S. history class. From 2001 to 2020, the exam positioned 50 multiple-choice questions with a chronological permutation of the survey course. I analyzed the exam over a two-decade period with 57 individual exams and 2,850 multiple-choice questions. The goal of this research was to interrogate an unsuspecting objective history of the United States as conveyed through this exam. Using a combination of critical theories to look for patterns and trends, I considered both hidden content and featured pillars of the survey course through the medium of the Part I multiple-choice. For included content, I asked if questions were phrased in a way that forced conclusions about certain events, such as the internment of thousands of Americans during World War II. I used discourse analysis to better understand the covert intentions of plural pronouns like we and people. The findings in Chapter 4 revealed that these collective pronouns were used to conceal oppressions against certain groups. The implications section of Chapter 5 deconstructed how the exam was tethered to a master narrative of the United States, and to a linear, progressive history that was unwilling to highlight oppressed voices or recognize unresolved, regressive, antidemocratic choices. For excluded content, I asked whose perspectives were continually missing. Which features were centered on political maps and which features were absent? Whose stories were central and whose stories were sacrificed to bolster a narrative about progress? How were advances for some disguised as advances for all, and at whose expense? What critical historical developments were omitted from the 2,850 questions? The findings are important for multiple reasons. First is that New York State officially committed its public education system to cultural responsiveness in 2019 with the New York State Culturally Responsive and Sustaining Education framework. How can curriculum meaningfully evolve in the future if educators do not fully understand the ways it was culturally irresponsive in the past? Second is that the survey U.S. history course is a powerful transmitter of knowledge about the story of the United States. Are we, as culturally responsive educators in New York, willing to extend the curriculum to include traditionally hidden developments, even if those developments interrogate and compromise the master narrative? Can we diversify the evidence, acknowledge regression, and clarify the specific beneficiaries of progress, thereby creating spaces for students to derive their own interpretations about the story and trajectory of the United States? These are difficult questions, yet educators can confront them more intentionally if we are willing to grapple with the complexities of the survey United States history course and the interaction between the discipline of history and the goals of nation building.
Keywords: New York State Regents exams; Survey high school history courses; High stakes testing; Master narrative; Culturally responsive and sustaining educationUnited States history curriculum